Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.drugpo.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of drug use during sex amongst MSM in Europe: Results from a multi-site bio-behavioural survey

Abstract: Substance and polydrug use during sexual encounters occurred amongst sampled MSM across Europe although varying greatly between study sites. Different local social norms within MSM communities may be important contextual drivers of drug use, highlighting the need for innovative and multi-faceted prevention measures to reduce HIV/STI risk in the context of drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
5
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 49 publications
4
68
5
9
Order By: Relevance
“…We examined the patterns of use of different RD types among Chinese MSM and the impact of such RD use on HIV high-risk behaviors and HIV acquisition. We found that the prevalence of polydrug use among Chinese MSM (5.0%) was lower than the reported prevalence of polydrug use among MSM in western high-income countries(~11.8%) [2]. Chinese MSM who used multiple RDs frequently used poppers along with one or more types of other RDs.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…We examined the patterns of use of different RD types among Chinese MSM and the impact of such RD use on HIV high-risk behaviors and HIV acquisition. We found that the prevalence of polydrug use among Chinese MSM (5.0%) was lower than the reported prevalence of polydrug use among MSM in western high-income countries(~11.8%) [2]. Chinese MSM who used multiple RDs frequently used poppers along with one or more types of other RDs.…”
Section: Discussioncontrasting
confidence: 60%
“…We found that 90% of MSM used poppers, and those who used multiple RDs frequently used poppers along with one or more types of other RDs (i.e., methamphetamine, ecstasy, codeine, or ketamine). Poppers are physiologically active substances that facilitate and enhance anal intercourse [2,12]. They do not affect the mental function or decision-making directly [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, 1.8% of an online survey of GBM reported recent IDU and 2.9% lifetime IDU . A European internet survey of GBM in 33 countries in 2010 found 5% report lifetime IDU , and a 2013–2014 survey of GBM in 13 European cities reported a similar lifetime injecting prevalence of 4.4% . Our prevalence of IDU among GBM therefore sits in the lower to mid‐range internationally.…”
Section: Discussionmentioning
confidence: 50%